2017
DOI: 10.3390/agronomy7040069
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Severity of Late Blight (Phytophthora infestans) and Improving Potato (Solanum tuberosum L.) Tuber Yield with Pre-Harvest Application of Calcium Nutrients

Abstract: Abstract:The efficiency of pre-harvest application of calcium chloride alone, calcium nitrate alone, and combined application of calcium chloride and calcium nitrate (1:1) was evaluated in reducing the severity of P. infestans and improving potato tuber yield. Pot experiment was conducted in randomized complete block design with four replications. The treatments consisted of combination of two potato varieties (Shenkola and Gera) and three types of calcium nutrients (calcium chloride alone, calcium nitrate alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…However, the latter treatment (T 3 ) reduced the overall AUDPC by 81% and increased tuber yield by 264% and 135% in 2017 and 2019, respectively, com- reported that these fungicides can reduce disease severity and increase the potato yield in subtropical plains of India. Additionally, the negative correlation between yield and AUDPC was evident in the present study, and our results are in agreement with earlier studied where different disease management options such as application of fungicides and calcium nutrients, that resulted in reduced late blight disease severity with significant improvement in the yield of crop (Dowley et al, 2008;Seifu, 2017;.…”
Section: Ta B L Esupporting
confidence: 93%
“…However, the latter treatment (T 3 ) reduced the overall AUDPC by 81% and increased tuber yield by 264% and 135% in 2017 and 2019, respectively, com- reported that these fungicides can reduce disease severity and increase the potato yield in subtropical plains of India. Additionally, the negative correlation between yield and AUDPC was evident in the present study, and our results are in agreement with earlier studied where different disease management options such as application of fungicides and calcium nutrients, that resulted in reduced late blight disease severity with significant improvement in the yield of crop (Dowley et al, 2008;Seifu, 2017;.…”
Section: Ta B L Esupporting
confidence: 93%
“…Disease symptoms started appearing on wild-type plants after ten days postinoculation (10dpi). We analyzed the WT plants for disease rating at 12dpi and observed 5% disease severity according to the scale described by Seifu [29]. Disease on stERF3-loss-of-function mutant plants has appeared on 23dpi, and at 28dpi, disease severity was 2%.…”
Section: Resultsmentioning
confidence: 99%
“…In planta disease assay and quanti cation of fungal biomass Seven-week-old full allelic edited plants and wild-type plants were inoculated with 2×10 4 sporangia ml -1. Disease severity was assessed according to Seifu [29]. For fungal biomass quanti cation, genomic DNA of infected leaves of knockouts and wild type plants was isolated using GeneJET genomic DNA Puri cation Kit (Thermo Scienti c, USA), and real-time qPCR analysis was performed using the primer pair PiO8-3-3Fwd/ PiO8-3-3Rev used by Llorente et al [30] to quantify the Phytophthora infestans biomass in potato.…”
Section: Detached Leaf Assaymentioning
confidence: 99%
“…Optimization of the nutritional status of potato with calcium nutrients can improve tuber yield quality and reduce different diseases [21,23,25,26,30]. Chitosan has a positive effect on the growth and potato tuber yield.…”
Section: Table 2 Influence Of Pre-planting and Foliar Treatment On The Growth And Development Of Potato Plants Infected Withmentioning
confidence: 99%
“…Calcium chloride was reported as a plant resistance inducer and an essential nutritional element in many species, such as tomato against powdery mildew [34], potato against late and early blight [21,23,35]. Arfaoui et al (2016) [36] indicated that pretreatment with calcium enhanced defense responses with higher levels of isoflavone phytoalexins in soybeans, thus reducing infection with Sclerotinia sclerotiorum, and suggesting an indirect impact on the pathogen.…”
Section: Dry Rot Disease Incidencementioning
confidence: 99%